The Future of Social Care From Problem to Rights-Based Sustainable Solution - Beresford, Peter (Edward Elgar Publishing, 2023)
In the face of major global demographic change, social care policy and practice are in urgent need of radical reform and reassessment. Rising poverty, inequality and pressure on local communities internationally, are also increasing the urgent need for reform. Drawing on the crisis-ridden UK experience as a case-study, this highly original book identifies the limits of the traditional welfare state in taking forward policy for the twenty-first century. The proposals amount to a renewed approach to social care, based on the philosophy of independent living as originally developed by the international disabled people's movement and subsequently embodied in a United Nations treaty applicable to all in need of care and support. Despite wide international sign up since adoption in 2008 there is little evidence of any nation successfully delivering. For the first time, this book offers both a blueprint for an environmentally sustainable, rights-based approach to social care and a practical route to achieving it.